Investigating Iraqi EFL Learners’ Awareness of Selected English Proverbs - Chassab Jabir, Azhar (Journal of College of Education, 2020)
Learning English as a foreign language does not refer to the mastery of the rules or merely the grammar of English . Rather , it refers to the full understanding of the semantic ( and syntactic ) concepts of that language , and employing this in real life situations . In this sense , the current research represents an attempt at investigating the Iraqi EFL Learners’ recognition and production of selected English proverbs . The study is divided into five sections ( an introduction , three sections and a conclusion ) . Evidence shows that English proverbs represent a very important component in learning English as a foreign language , and that Iraqi EFL learners face considerable difficulties in understanding and employing them in real life situations .